2018
DOI: 10.1371/journal.pone.0201024
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression profiling of the auxin response factor (ARF) gene family in physic nut

Abstract: Auxin response factors (ARF) are important transcription factors which mediate the transcription of auxin responsive genes by binding directly to auxin response elements (AuxREs) found in the promoter regions of these genes. To date, no information has been available about the genome-wide organization of the ARF transcription factor family in physic nut. In this study, 17 ARF genes (JcARFs) are identified in the physic nut genome. A detailed investigation into the physic nut ARF gene family is performed, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Auxin signaling is known to regulate the expression of early/primary auxin response genes through ARFs. Previous studies have already identified members of the ARF family in crops with economic values ( Wang et al., 2007 ; Kumar et al., 2011 ; Xing et al., 2011 ; Luo et al., 2014 ; Wan et al., 2014 ; Shen et al., 2015 ; Hu et al., 2015 ; Liu et al., 2015 ; Singh et al., 2017 ; Tang et al., 2018 ). According to the Plant Transcription Factor Database ( ), 4,578 members of the ARF gene family exist in the genomes of different plant species in varying numbers; papaya (10), tomato (22), Arabidopsis (37), banana (50), and durian (77).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Auxin signaling is known to regulate the expression of early/primary auxin response genes through ARFs. Previous studies have already identified members of the ARF family in crops with economic values ( Wang et al., 2007 ; Kumar et al., 2011 ; Xing et al., 2011 ; Luo et al., 2014 ; Wan et al., 2014 ; Shen et al., 2015 ; Hu et al., 2015 ; Liu et al., 2015 ; Singh et al., 2017 ; Tang et al., 2018 ). According to the Plant Transcription Factor Database ( ), 4,578 members of the ARF gene family exist in the genomes of different plant species in varying numbers; papaya (10), tomato (22), Arabidopsis (37), banana (50), and durian (77).…”
Section: Discussionmentioning
confidence: 99%
“…The domain architecture of ARFs is known to play a key role in their specificity. Since the identification and characterization of the first Arabidopsis ARF ( AtARF1 ) ( Ulmasov et al., 1997 ), numerous studies have identified members of the ARF gene family in plant species, such as tomato ( Kumar et al., 2011 ), rice ( Wang et al., 2007 ), Medicago ( Shen et al., 2015 ), banana ( Hu et al., 2015 ), apple ( Luo et al., 2014 ), maize ( Xing et al., 2011 ), chickpea ( Singh et al., 2017 ), physic nut ( Tang et al., 2018 ), grape ( Wan et al., 2014 ), and papaya ( Liu et al., 2015 ). Functional characterization of some ARFs based on the phenotypes of the loss-of-function and gain-of-function mutants have also been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Since ARF1, the first Arabidopsis ARF gene, was cloned and its function investigated [6], the ARF gene family has been identified and well characterized in many crop species, including tomato (Solanum lycopersicum), maize (Zea mays), rice (Oryza sativa), poplar (Populus trichocarpa), Chinese cabbage (Brassica rapa), banana (Musa sp.) and physic nut (Jatropha curcas L.) [4,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Exon/intron analysis could provide some valuable information regarding the evolutionary relationships among plant taxa [ 36 ]. Therefore, this study investigated and compared the exon/intron structures of YABBY genes among these seven magnoliids species.…”
Section: Resultsmentioning
confidence: 99%
“…YABBY genes are small and essential key regulators that are specifically related to the evolution of leaves in seed plants that encode a C2C2 zinc-finger domain at the N-terminal region and a conserved YABBY domain in the C-terminal region with a helix–loop–helix motif [ 37 , 38 ]. In terms of basal angiosperms, five YABBY genes have been identified in Amborella , Cabomba, and Nymphaea [ 36 ]. In addition, six YABBY genes have been described in the model plant Arabidopsis , and eight have been identified in Oryza [ 20 , 21 , 22 , 37 ].…”
Section: Discussionmentioning
confidence: 99%